The Influence of Pro-Environmental Behavior and Green Organizational Culture on Sustainable Performance: Evidence from Cafés in Ternate City - Dilsya Fiana Marjan; Marwan Man Soleman; Adnan Rajak (International Journal of Business, Law, and Education, 2026)
Purpose - This study examines the effect of pro-environmental behavior and green organizational culture on the sustainable performance of cafés in Ternate City. Design/methodology /approach - The study employed a quantitative explanatory design. Data were collected through structured questionnaires distributed to 29 operational employees of cafés that had implemented environmentally oriented practices. The data were analyzed using validity and reliability testing, classical assumption testing, and multiple linear regression in SPSS. Findings - The regression results indicate that pro-environmental behavior has a positive but statistically non-significant effect on sustainable performance (B = 0.170; p = 0.238). In contrast, green organizational culture has a positive and significant effect on sustainable performance (B = 1.063; p = 0.001). The simultaneous test confirms that pro-environmental behavior and green organizational culture jointly influence sustainable performance (F = 21.541; p = 0.001), with an estimated coefficient of determination of 0.624. Originality/value - The study extends sustainability management research by focusing on small service businesses in an island-city context, where resource efficiency, waste reduction, and environmentally responsible work routines are directly relevant to business continuity. The findings suggest that individual green behavior may not be sufficient unless it is embedded in a supportive green organizational culture.